PENGARUH KUALITAS, HARGA, CITRA MEREK DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI DISTRO INDIGO JOMBANG - Achmad Fikri Hanif; N. Rachma (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTThe study was conducted to analyze the factors that affect consumers inmaking purchasing decisions on Indigo product at Indigo store, Jombang. Theproblem in this study is a decline sales in Indigo product for 3 months at Indigostore, Jombang. Independent variables consist of Quality (X1), Price (X2), BrandImage (X3), and Product design (X4) In the other hand, the dependent variable isthe Buying Decision (Y). In this study, observer take 100 respondents that weretaken by using a purposive sampling technique. Analysis using SPSS 16.0,including, reliability test, validity test, classic assumptions test, multipleregression analysis, hypothesis testing via the F and T test, and analysis of thecoefficient of determination (R ²). From the analysis of the regression equationwas obtained:Prices showed the greatest regression coefficient. Price is the mostimportant factor influencing the purchase decisions of consumers who buy Indigoproduct at Indigo store, Jombang. The third important factor is the brand imageand product design as the fourth factors that influence the purchase decision.study.Keywords: Quality, Price, Brand image, Product design, PurchaseDecision